Advancing the Sustainability of US Agriculture through Long‐Term Research. Issue 6 (1st November 2018) - Kleinman, P. J. A.; Spiegal, S.; Rigby, J. R.; Goslee, S. C.; Baker, J. M.; Bestelmeyer, B. T.; Boughton, R. K.; Bryant, R. B.; Cavigelli, M. A.; Derner, J. D.; Duncan, E. W.; Goodrich, D. C.; et al.
Abstract : Agriculture in the United States must respond to escalating demands for productivity and efficiency, as well as pressures to improve its stewardship of natural resources. Growing global population and changing diets, combined with a greater societal awareness of agriculture's role in delivering ecosystem services beyond food, feed, fiber, and energy production, require a comprehensive perspective on where and how US agriculture can be sustainably intensified, that is, made more productive without exacerbating local and off‐site environmental concerns. The USDA's Long‐Term Agroecosystem Research (LTAR) network is composed of 18 locations distributed across the contiguous United States working together to integrate national and local agricultural priorities and advance the sustainable intensification of US agriculture. We explore here the concept of sustainable intensification as a framework for defining strategies to enhance production, environmental, and rural prosperity outcomes from agricultural systems. We also elucidate the diversity of factors that have shaped the past and present conditions of cropland, rangeland, and pastureland agroecosystems represented by the LTAR network and identify priorities for research in the areas of production, resource conservation and environmental quality, and rural prosperity. Ultimately, integrated long‐term research on sustainable intensification at the national scale is critical to developing practices and programs that can anticipate and address challenges before they become crises. Core Ideas: The LTAR network was established to enhance the sustainability of US agriculture. The LTAR "common experiment" compares business as usual with aspirational management. LTAR sites contribute research observations to the network's database. LTAR network research will support sustainable intensification strategies.